A produção acadêmica sobre a formação continuada de professores de educação física - Cruz Junior, Antônio Fernandes da (2010)
This research focuses on the following question: what would be the conception of continuing education which prevails in the studies of physical education? We therefore investigated the production of articles materialized in four mainly journals: Revista Movimento, Revista Brasileira de Ciências do Esporte, Revista Motriz e Revista Pensar a Prática. Our hypothesis is that when discussing the work area, we would find a variety of concepts which, in most cases, converge to a narrow understanding of continuing formation, based on the prioritization of the concept of immediate practical, the reflectivity from the micro and Intraschool issues. Analyzing the theoretical categories (experience, teacher‟s knowledge, pedagogical practice and qualitative research) that guide the discussion of continuing education in this study, we realized that these fundamental concepts instigate advances and at the same time limitations and problems. Despite no reduction in continuing formation to a single event, the critique of instrumental rationality in teaching, the attempt to build alternative routes to speeches merely macro, the appreciation of the role of the teacher and reflective practice, the academic study enhances understanding of immediate practical, values the knowledge that is useful for teaching situation, replaces the experience by experience, instrumentalizes the theory and loses the historical horizon. Therefore, the reflections on continuing education of teachers assume in many times aspects of semiformation. Faced with many leaps and bounds as stated, we should strengthen the argument that we stand for: that continuing formation should not exclude an extensive cultural formation.